Non-uniform distribution of sulfur vapor and its influence on Cu2ZnSnS4 thin film solar cells. (15th November 2019) - Zhang, Yanwei; Wang, Shenwei; Huang, Miaoling; Ou, Kai; Bai, Liyuan; Zhang, Kexin; Yi, Lixin
Highlights: Non-uniform distribution of sulfur vapor in furnace chamber was revealed. Properties of the CZTS thin films are optimized by adjusting the positions in chamber. Device parameters of solar cells are influenced by the sulfur partial pressure. Reasons accounts for the non-uniform distribution of sulfur vapor were illustrated. Abstract: The morphological, compositional and structural properties of the Cu2 ZnSnS4 (CZTS) thin films and the device parameters of solar cells are strongly influenced by the sulfur partial pressure during the sulfurization process. To investigate the distribution of sulfur vapors along the sulfurization chamber, the uniformity of the CZTS thin films and solar cells during sulfurization process, several same samples were sequentially placed in the chamber. The device performance of CZTS thin film solar cells shows a strong correlation with the positions in the sulfurization zone and the morphologies of the CZTS thin films. An optimal position was found in the sulfurization furnace where could improve the crystallinity of CZTS thin films, reduce the formation of secondary phases, and improve the efficiency of solar cells. The best solar cell in the optimal position shows an efficiency of 3.49%, which was restrained by the Sn loss. The possible reasons for the non-uniform distribution of sulfur vapor are analyzed.